The balance of nature : ecology's enduring myth - Kricher, John C. (Princeton University Press, 2009)
The idea of a balance of nature has been a dominant part of Western philosophy since before Aristotle, and it persists in the public imagination and even among some ecologists today. In this lively and thought-provoking book, John Kricher demonstrates that nature in fact is not in balance, nor has it ever been at any stage in Earth's history. He explains how and why this notion of a natural world in balance has endured for so long, and he shows why, in these times of extraordinary human influence on the planet's ecosystems, it is critical that we accept and understand that evolution is a fact.